Methods of wintering yearling steers on bluestem pasture, 1951-52. - Smith, E.F.; Cox, R.F.; Fansher, S.B. (Kansas Agricultural Experiment Station, 2012)
Thirty head of good quality, about 750-pound, Hereford yearling steers were used in the test which was started December 7, 1951. The steers were purchased in the spring of 1951 and had been grazed on bluestem pasture during the summer and fall. They carried a moderate amount of flesh. They lost some flesh during October and November when they were on grass alone prior to the start of winter tests. The steers were sprayed twice with B.H.C. for lice. All of the pastures in which the steers were wintered had been grazed the previous summer at normal stocking rates, but a plentiful supply of dry grass remained. From 6 to 13 acres of pasture were allowed each steer. The 30 steers were divided into three lots of 10 steers each and received the following supplements in addition to dry bluestem pasture from December 7, 1951, to April 29, 1952. Lot 1-2 pounds of cottonseed oil meal pellets daily, salt, and mineral (bonemeal and salt). Lot' 2-4 pounds of cottonseed oil meal pellets every other day (average 2 pounds a day), salt, and mineral (bonemeal and salt). Lot 3-Cottonseed oil meal and salt self-fed, and mineral (bonemeal and salt). (The salt was mixed with the cottonseed oil meal to limit its consumption and make it possible to self-feed the cottonseed oil meal. This mixture was fed in a self-feeder.) The cottonseed oil meal pellets were fed on the ground.
Keywords: Beef; Yearling steers; Stocking rate; Cottonseed; Gain